2011
DOI: 10.1016/j.jcm.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of the addition of the Pilates method over a minimal intervention in the treatment of chronic nonspecific low back pain: a study protocol of a randomized controlled trial

Abstract: Objective: There is little high-quality evidence on the efficacy of the Pilates-based exercises for the treatment of chronic nonspecific low back pain. Therefore, the objective of this paper is to present a study protocol to investigate the efficacy of adding Pilates-based exercises to a minimum intervention in patients with chronic non-specific low back pain. Methods: This randomized controlled trial will recruit 86 patients of both sexes, aged between 18 and 60 years, with chronic non-specific low back pain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
11
1
3
Order By: Relevance
“…Nestes casos, o controle de intensidade e nível do esforço, são tipicamente realizados de maneira subjetiva, pelo profissional que ministra a prática (no momento em que o executante realiza um determinado movimento, fica a cargo do profissional, identificar se o exercício está sendo realizado corretamente, ou seja, sem a existência de compensações posturais, o que possibilitaria o aumento do nível de esforço) [20][21][22] .…”
Section: Discussionunclassified
“…Nestes casos, o controle de intensidade e nível do esforço, são tipicamente realizados de maneira subjetiva, pelo profissional que ministra a prática (no momento em que o executante realiza um determinado movimento, fica a cargo do profissional, identificar se o exercício está sendo realizado corretamente, ou seja, sem a existência de compensações posturais, o que possibilitaria o aumento do nível de esforço) [20][21][22] .…”
Section: Discussionunclassified
“…However the most suitable method of exercise in the treatment of LBP has been widely debated [6][7][8][9][10]. Recently Pilates based exercises have been increasingly incorporated into physiotherapy rehabilitation programmes [11]. The Pilates technique focuses on the principles of centring, postural alignment, co-ordination, concentration, breathing, precision and movement sequencing [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested that Pilates based exercise incorporates lumbar stabilisation training within dynamic and functional movement [13,[16][17]. Lumbar stabilisation in a functional context may be key to improving patient self-efficacy and reducing fear avoidance [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of Pilates has stimulated the development of studies investigating its effectiveness, evaluating the effects of training programs on different parameters such as muscle strength and muscle endurance (1,2), lexibility (3,4), decreased pain (5,6), joint function restoration (5, 7) among others. Given the positive results, the method has been increasingly indicated and used in training and orthopedic rehabilitation programs, with emphasis on the rehabilitation of lower limbs (7,8).…”
Section: Introductionmentioning
confidence: 99%